Significance of liquid inclusions in the C-O-H fluid system of the upper zone, Bushveld Igneous Complex, South Africa - Buthelezi, Musawenkosi (My University, 2018)
Fluid inclusions in the Upper Zone quartz of the Bellevue drillcore and quartz of the monzonite/two-feldspar granite from the Stoffberg area are studied by a suite of advanced high precision methods. The accessory magmatic quartz of the Bellevue drillcore samples hosts a complex suite of H2O-CO2-CH4 fluid inclusions which have thus far received very little attention. For the abundant quartz in the Stoffberg samples (quartz monzonite/two-feldspar granite) hosts a simple suite of H2O-NaCl, H2O-CaCl2 and H2O-MgCl2 fluid inclusions, which is yet to be described. CH4-rich fluid inclusions of the Bellevue drillcore (e.g. olivine ferrodiorite, quartz anorthosite, anorthosite and leucogabbronorite) can be shown based on fluid inclusion petrography to be mainly part of the primary fluid inclusion assemblage. Based on conducted study four types of fluids were identified in Bellevue drillcore, all of them separated during the crystallization of volatile-rich residual melt of original mafic magma, whilst in the Stoffberg samples only three types of fluids were identified and are likely to be derivatives of the later felsic melts, probably of crustal melts. The melting temperatures of the carbonic (CO2 ± CH4) of olivine ferrodiorites and leucogabbronorites, ranges from -59.7 to 56.8 ºC (mean = 58 ± 0.9 ºC; n=50), fluid inclusions, with their homogenization temperatures (TCO2) ranging from 18.8 to 30 ºC (28 ± 3.6 ºC). The number of carbonic (CO2 and CH4) fluid inclusions in the Bellevue drillcore suggests that the carbonic (CO2 and CH4) fluids played a significant role, by acting as a geochemical barrier in shallow magmatic systems, which is contrary to the generally accepted idea that carbonic fluids are generally not a major component in such magmatic systems as these fluids tend to escape from magma at relatively deep environments. For the Stoffberg samples there is no evidence for carbonic (CO2 and CH4) fluid inclusions, which may imply that (CO2 and CH4) fluids played no part during the crystallization and cooling of the Stoffberg rocks. The Ti-in-quartz geothermometry suggests that the maximum temperature of entrapment from about 677 ± 29 to 767 ± 18ºC and 738 ± 35 and 799 ± 22°C, at 3 kbar pressure, for the Bellevue core and Stoffberg samples, respectively. Based on the microthermometric, geochemical (Ti-in-quartz geothermometry) and petrographic evidence, the CH4 observed in the samples of the Bellevue drillcore was produced by respeciation of the C-O-H fluids via in situ phase separation (immiscibility of the fluids in the H2O-CO2-CH4 system) and probably the interaction of fluids with rocks during the late-stages of crystallization in the Bushveld Igneous Complex (BIC). This is further supported by the presence of graphite in H2O-CO2 bearing inclusions, in quartz anorthosite and leucogabbronorite. The lower melting temperature of aqueous-rich fluid inclusions, in olivine ferrodiorites and quartz anorthosites, suggest a later entrapment along cracks in quartz. This study further emphasizes the idea that the oxidation of reduced heterophase fluids could be the most important geochemical barrier caused the crystallization of solid mineral phases from heterophase fluids. The evidence presented in this study suggest that the Stoffberg material is unlikely to represent the most evolved part of the Rustenburg Layered Suite as previously suggested, but represents relic products of the Lebowa Granite Suite or crustal melts into which the Bushveld Igneous Complex intruded into.
Keywords: Fluid inclusions--South Africa; Mineralogy; Fluid inclusions